2014
DOI: 10.1136/jnnp-2014-308241
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord grey matter abnormalities are associated with secondary progression and physical disability in multiple sclerosis

Abstract: The study findings suggest that pathological involvement of the spinal cord GM contributes significantly to physical disability in relapse-onset MS and SPMS in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 37 publications
7
59
1
Order By: Relevance
“…CSA and GBSI provided similar rates of spinal cord atrophy in each MS subtype, but CSA yielded a larger variability (standard deviation) when compared with GBSI (eg, in RRMS AE4.02% vs AE2.57%, respectively), implying that GBSI measurements are more precise. [3][4][5] In line with this, the percentage spinal cord decline measured with GBSI was associated with EDSS progression and with disease subtype, and performed better than CSA-derived spinal cord atrophy in detecting more disabled patients. 34 Of note, a higher percentage of spinal cord decline (and a lower standard deviation) was found in PMS when using GBSI than when using CSA (−2.29 AE 2.40% vs −1.29 AE 3.20%), and this was probably due to the relatively small sample in this MS subtype, further highlighting the higher measurement precision of GBSI.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…CSA and GBSI provided similar rates of spinal cord atrophy in each MS subtype, but CSA yielded a larger variability (standard deviation) when compared with GBSI (eg, in RRMS AE4.02% vs AE2.57%, respectively), implying that GBSI measurements are more precise. [3][4][5] In line with this, the percentage spinal cord decline measured with GBSI was associated with EDSS progression and with disease subtype, and performed better than CSA-derived spinal cord atrophy in detecting more disabled patients. 34 Of note, a higher percentage of spinal cord decline (and a lower standard deviation) was found in PMS when using GBSI than when using CSA (−2.29 AE 2.40% vs −1.29 AE 3.20%), and this was probably due to the relatively small sample in this MS subtype, further highlighting the higher measurement precision of GBSI.…”
Section: Discussionsupporting
confidence: 60%
“…The rates of spinal cord loss over 1 year obtained with GBSI were similar to those obtained with CSA, but they were associated with lower variability, greater ability to distinguish between MS patients and controls, and more robust clinical correlates, thereby holding promise for future MS research on spinal cord imaging. [3][4][5] Spinal cord atrophy occurs from the early stages of MS (eg, CIS), is more obvious in progressive patients than relapsing types of MS, and progresses faster than brain atrophy. CSA and GBSI provided similar rates of spinal cord atrophy in each MS subtype, but CSA yielded a larger variability (standard deviation) when compared with GBSI (eg, in RRMS AE4.02% vs AE2.57%, respectively), implying that GBSI measurements are more precise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated a high association with MS disability, particularly in progressive MS. 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, manual grey matter (GM) outlining was carried out on the average DW volume obtained according to the procedure described in Kearney et al (2014). The GM and WM masks were obtained directly from the manually drawn outlines and were limited to voxels within the whole-cord mask.…”
Section: Segmentationmentioning
confidence: 99%